Bauran Promosi Sebagai Media Komunikasi Pasca Pandemi Covid 19 pada Syuger Café - Susilowati, Isnurrini Hidayat (www.bsi.ac.id, 2023)
The pandemic of Covid 19 occurred since 2020 has caused many sectors affected, such as the culinary sector, its market not only in beverage products but also foods which are currently mostly vintage. The concept chosen by millennials whose hobby of looking for aesthetic photo locations. To be able to maintain and develop a culinary business, a marketing strategy is needed, especially proper promotion after the pandemic of Covid 19. Syuger Café is able to compete in carrying out the promotion mix. The purpose of this study is to determine the marketing mix strategies of Syuger Café. This study uses a qualitative descriptive method and quantitative by analyzing the promotion mix strategies. With the promotion mix strategy, the sales will increase in the next period. The results of the study found that Syuger Café has carried out all promotional strategies based on the promotion mix as a medium of communication to the public. . Sales promotions about discount programs uploaded via Instagram have become an important component of the promotional mix at Syuger Café after the Covid 19 Pandemic by informing them of competitive prices and the existence of discount promos. Promotions from indiviuals can be more effective because marketers can touch consumers' emotions so that it is expected to expand the market and form the loyal consumer. After the marketing mix strategy is carried out, sales forecasting is carried out for the February 2023 period with results using the 3 monthly Moving Average method better than the Exponential Smoothing method. Keywords : The Promotion Mix, Communication Media, Semi Average and Exponential Smoothing.